Optimizing the content and gradation of recycled tyre rubber particles to improve cracking resistance of concrete mortars - Tsoana, Molefe Donald (Department of Civil Engineering, 2015)
Concrete structures are designed to be sustained for a specific service life time. When some of these structures age, they undergo deterioration due to their exposure to harsh environmental conditions and thus their structural and aesthetic functionalities get compromised. In order to restore such functionalities, concrete structures can be rehabilitated or repaired using concrete mortars as overlays (Vaysburd et al., 2012). On application, the concrete mortars usually experience substantial differential shrinkage that causes the build-up of internal tensile stress. Shrinkage cracking often happens if the concrete mortar does not exhibit sufficient tensile strength to sustain these stresses. The ingress of aggressive agents that may cause further deterioration on structure becomes easier (Shazali et al., 2012). The cracking resistance of concrete mortars has thus become a major concern in repair and rehabilitation of concrete structures. The literature suggests that the performance of concrete mortars could be improved by enhancing the material properties that influence their cracking resistance. A large amount of research exists pertaining to the use of rubber particles in concrete mixes to improve their cracking resistance. However, no research was found regarding the influence of optimizing recycled tyre rubber particle grading and content in concrete mortar mixes in particular. This research investigated the influence of optimizing recycled tyre rubber particle grading and content in various concrete mortar mixes to improve their cracking resistance.